(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The awareness level of children at the elementary school toward their surroundings is currently decreasing, it caused by the increasing use of gadgets. Naturalist intelligence of elementary school students who have a role in caring for their surroundings. Plant cultivation activities are one way to improve naturalist intelligence in children. Apart from that, there is a need for student abilities related to entrepreneurship to support students’ life skills. The target audience for this program is students of the Mulia Bakti Purwokerto Elementary School which is managed by the GUSDURian Banyumas Education Foundation. The aim of this community service activity is to increase students’ naturalistic intelligence through organic cultivation of vegetables and tropical fruit, as well as applying student entrepreneurship through post-harvest activities. The method implemented in this service activity is a participatory method. The target audience is invited to play an active role in practical vegetable cultivation activities from seeding to harvest, planting tropical fruit plants, and post-harvest handling from packaging to marketing through online bazaar activities carried out by students. As a result, students’ skills increase in terms of plant cultivation and post-harvest management. The ability to work together and understand the surroundings increases during the activity process through group formation during the activity. Entrepreneurship skills increase with online bazaar activities to market students’ harvests in each group. — Tingkat keperdulian anak pada tingkat sekolah dasar terhadap sekitar sekarang ini mulai menurun, karena meningkatnya penggunaan gawai. Kecerdasan naturalis pada siswa SD yang memiliki peran terhadap keperdulian pada sekitar. Kegiatan budidaya tanaman menjadi salah satu cara untuk memperbaiki kecerdasan naturalis pada anak. Selain itu, perlu adanya kemampuan siswa terkait entrepreneurship untuk menunjang life skill siswa. Khalayak sasaran kegiatan program ini adalah siswa Sekolah Dasar Mulia Bakti Purwokerto yang dikelola oleh Yayasan Pendidikan GUSDURian Banyumas. Tujuan kegiatan pengabdian kepada masyarakat ini adalah meningkatkan kecerdasan naturalis siswa melalui kegiatan budidaya tanaman sayur dan buah tropis secara organik, serta mengaplikasikan entrepreneurship siswa melalui kegiatan pasca panen. Metode yang dilaksanakan dalam kegiatan pengabdian ini adalah metode partisipatif. Khalayak sasaran diajak berperan aktif dalam kegiatan budidaya tanaman sayur praktik mulai dari persemaian hingga panen, penanaman tanaman buah tropis, dan penanganan pasca panen mulai dari pengemasan hingga pemasaran melalui kegiatan bazar daring yang dilakukan oleh siswa. Hasilnya keterampilan siswa meningkat dalam hal budidaya tanaman dan pengelolaan pasca panen. Kemampuan bekerja sama dan memahami sekitarnya meningkat selama proses kegiatan melalui pembentukan kelompok selama kegiatan berlangsung. Keterampilan mengenai entrepreneurship meningkat dengan adanya kegiatan bazar daring untuk memasarkan hasil panen siswa pada setiap kelompoknya.